Pengaruh Media Pembelajaran Berbasis Video Terhadap Perkembangan Kognitif Siswa di UPTD SMPN 16 Mandai Maros Sulawesi Selatan - Juprianto, Juprianto; Wijaya, Hengki; Supartini, Tri; Hana, Sarce Rien (Sekolah Tinggi Teologi Immanuel Sintang Kal-Bar, 2023)
The problem in this study is the lack of understanding of students' learning in understanding lessons on the cognitive shutter. This is indicated by the management of the class that uses the lecture method more, causing students to be less active in taking lessons well. This study aims to determine the extent of the influence of Vodeo-Based Learning Media on the cognitive development of students at UPTD SMPN 16 Mandai Maros, South Sulawesi. The method used in this research is classroom action research method by collecting the following data: First, literature study to find theories of video-based learning media and cognitive development. Second, field observations to find out directly the problems that occur in the field and directly apply video-based learning media to overcome existing problems. Third, distributing questionnaires after students leave school with a scale of 1-4 with the aim of knowing the extent of students' cognitive development. After the data is collected, the data is analyzed and correlated to get the expected results. The results of the correlation analysis of video-based learning media on the cognitive development of students at UPTD SMPN 16 Mandai Maros, South Sulawesi, obtained a correlation coefficient of 0.098 with a p-value of 0.546. From the results of the correlation coefficient shows that r count is smaller than r table (0.098 < 0.312). So it can be concluded that the correlation coefficient, it can be seen that the relationship between video-based learning media on students' cognitive development is very low or very weak.